ANALISIS PUTUSAN MAHKAMAH AGUNG ATAS PEMBUKTIAN ITIKAD TIDAK BAIK DALAM PENDAFTARAN MEREK - NINDYA SARI USMAN (PREMISE LAW JURNAL, 2015)
A brand is a symbol of a product which is used to introduce a product produced by a company to people in the market. It plays a very important role for its owner. Registering a product has to be done with good faith because if it is done with bad faith, the registration will be rejected by the Directorate General of HaKI and can be canceled by the Court after the legitimate owner have filed a complaint. The study used judicial normative method. Legal protection for famous brands and for brand registrants with good faith is stipulated in Law No. 15/2001 on Brand, and its legal enforcement is through the hearing in Court, from the Commercial Court to cassation appeal to the Supreme Court. Nevertheless, the Ruling of the Supreme Court in giving legal protection for famous brands and for brand registrants with good faith is usually inconsistent. Keywords: Ruling of the Supreme Court, Bad Faith, Brand Registration